2021
DOI: 10.1093/jhps/hnab048
|View full text |Cite
|
Sign up to set email alerts
|

Opioid overprescription in adolescents and young adults undergoing hip arthroscopy

Abstract: Few studies have examined factors related to the increased consumption of opioids after hip arthroscopy in adolescents and young adults. This study sought to determine prescription patterns following hip arthroscopy in this population, and to determine clinical or surgical factors associated with increased post-operative opioid use. Daily post-operative opioid intake was obtained from pain-control logbooks of adolescents and young adults who underwent hip arthroscopy between January 2017 and 2020. Study outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Hence, there is concern that opioids are overprescribed postoperatively. In a study of adolescents and young adults asked to log their pain control after hip arthroscopy, patients consumed an average of only 20% of the opioid tablets prescribed 16. A similar study of 100 patients undergoing knee arthroscopy demonstrated that patients used only 32.4% of prescribed tablets, with 11 patients taking none of their prescribed opioids 17.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, there is concern that opioids are overprescribed postoperatively. In a study of adolescents and young adults asked to log their pain control after hip arthroscopy, patients consumed an average of only 20% of the opioid tablets prescribed 16. A similar study of 100 patients undergoing knee arthroscopy demonstrated that patients used only 32.4% of prescribed tablets, with 11 patients taking none of their prescribed opioids 17.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of adolescents and young adults asked to log their pain control after hip arthroscopy, patients consumed an average of only 20% of the opioid tablets prescribed. 16 A similar study of 100 patients undergoing knee arthroscopy demonstrated that patients used only 32.4% of prescribed tablets, with 11 patients taking none of their prescribed opioids. 17 Although most patients only use as much pain medication as they need, others may continue using their opioid prescription even after their pain becomes less severe.…”
Section: Postoperative Opioid Use and The Potential For Marijuanamentioning
confidence: 99%
See 1 more Smart Citation
“…Two weeks after discharge, we invited eligible patients via email to complete a web‐based REDCap survey (Supplement S1). We selected this time point based on prior studies suggesting that up to 96.8% of patients cease using opioids by 2 weeks after discharge 41–43 . For outpatient surgery, the discharge date was the same as the surgery date.…”
Section: Methodsmentioning
confidence: 99%
“…We selected this time point based on prior studies suggesting that up to 96.8% of patients cease using opioids by 2 weeks after discharge. [41][42][43] For outpatient surgery, the discharge date was the same as the surgery date. For inpatient surgery, we used the discharge date to ensure patients had an adequate amount of time to use their opioids at home.…”
Section: Study Setting Participants and Designmentioning
confidence: 99%